PERBEDAAN KEMANDIRIAN LANSIA YANG TINGGAL DI PANTI WREDHA DAN YANG TINGGAL BERSAMA KELUARGANYA - Lilis Lismayanti; Angga Riadi Permana; Rizky Aulia Rachman (Journal Prima Health Science, 2020)
The better health services in Indonesia have a positive impact on increasing life expectancy, so thenumber of older adults in Indonesia continues to increase. Physiologically the elderly will be faced withproblems related to degenerative diseases, most of which will affect the fulfillment of their daily needs.There is an older adult who lives with his family, lives nursing home, and lives in a home, which, ofcourse, will affect his independence. By knowing the differences in the level of independence of theelderly who live in a nursing home and who live with their families, can provide direction in developingmodels of nursing care so that the elderly are more productive in their old age. This study aims todetermine the differences in the level of independence of the elderly who live in a nursing home with thosewho live with their families. This type of research uses comparative explanatory studies with surveymethods. The study population was 1012 older adults in Cikadongdong Village. The sample size usessample estimates for hypothesis testing of the two paired populations determined by 32 elderly in theorphanage and 32 who live with the family. The sampling technique uses individual matching between thetwo groups. The instrument uses the Barthel Index. Data analysis method using independent sample Ttest.The results showed that the data were normally distributed, the results of statistical tests showed thatthere was a significant difference between the level of independence of the elderly living in nursing homewith those living with their families with a p-value of 0,000, where families living with their families weremore independent than those living in nursing homes. It is recommended that nurses educate nursinghome administrators to implement nursing care tailored to the needs of the elderly and consider the levelof independence of the elderly. So that the elderly will optimize their independence to meet their dailyneeds.